Estimating unsaturated hydraulic conductivity of cocopeat-perlite mixtures using RETC software - Fazlil Ilahi, Wan Fazilah; Rosdi, Nur Syaffiqa Izleen; Zainuddin, Safwah Adani (UMK Press, 2025)
Cocopeat in soilless culture needs to be mixed with other coarser substrates to increase the aeration medium. Hydraulic conductivity measures the ability of a fluid to flow through pore spaces under both saturated and unsaturated conditions. This study focused on estimating cocopeat-perlite unsaturated hydraulic conductivity using RETC software. Six (6) treatments were used, 100% cocopeat act as control treatment (T1), while treatments with different cocopeat-perlite ratios (T2=3 cocopeat:1 perlite; T3=2 cocopeat:1 perlite; T4=1 cocopeat:1 perlite; T5=1 cocopeat:2 perlite; T6=1 cocopeat:3 perlite) has been used for cocopeat-perlite unsaturated conductivity determination. Results obtained were compared using van Genuchten–Mualem model (VGM), van Genuchten–Burdine (VGB) and Brooks-and-Corey model (BC) with RETC software. As the perlite ratio increases, the rate of change in hydraulic conductivity also rises due to enhanced substrate porosity, thereby improving aeration around plant roots. T2 and T3 served as aeration improvement for cocopeat medium without rapid water loss in crop cultivation. In comparing results in BC and VGM, the derivation of hydraulic conductivity increases as approaches the saturation point. However, to obtain accurate results when n is larger than 2, the VGM was preferable due to no bubbling pressure effect that may result in discontinuity near slopes at saturation point. Thus, by understanding the effects on the cocopeat-perlite ratio, the substrate properties can be optimized to balance water retention and aeration according to specific horticultural needs. The ability to improve root zone aeration without compromising water availability highlights the potential of tailored cocopeat-perlite mixes to encourage greater crop yields in controlled environment agriculture.